Implementação de um roteador em um computador executando o sistema operacional Linux - Lobato, André de Macedo Portugal (2012)
This work describes the implementation of a router on a computer comprised of only a motherboard, a processor, RAM memory and network interfaces, with no local storage units, booted and configured from the network. This computer runs Tiny Core Linux distribution of Linux operating system and Quagga, a software suite that implements routing protocols. Tiny Core Linux and Quagga are presented. The procedures of customizing the image file of Tiny Core Linux, to include Quagga and other necessary extensions, and of configuring a server, where the computer functioning as a router boots and is configured from, are described. The test of a computer functioning as a router, on a network with, beyond this computer and the server, an ADSL modem with an integrated router and a user’s computer, is also described. The test shows that Quagga can communicate with another router and that the computer functioning as a router can have little RAM memory.